Cobalt‐Catalyzed Intermolecular C(sp2)O Cross‐Coupling. Issue 24 (29th April 2015) - Kundu, Debasish; Tripathy, Manisha; Maity, Pintu; Ranu, Brindaban C.
Abstract Cobalt(II)‐catalyzed C(sp2)O cross‐coupling between aryl/heteroaryl alcohols and vinyl/aryl halides in the presence of CuI has been achieved under ligand‐free conditions. In this reaction, copper plays a significant role in transmetalation rather than being directly involved in the CO coupling. This unique Co/Cu‐dual catalyst system provides an easy access to a library of aryl–vinyl, heteroaryl–styryl, aryl–aryl, and heteroaryl–heteroaryl ethers in the absence of any ligand or additive.